Biosensing: how citizens' views illuminate emerging health and social risks. (1st February 2016) - Mort, Maggie; Mary Roberts, Celia; Furbo, Mette Kragh; Wilkinson, Joann; Mackenzie, Adrian
Abstract : This article explores material from a citizen's inquiry into the social and ethical implications of health biosensors. In 'Our Bodies, Our Data' a space was afforded for members of the public to examine two forms of health biosensing, and for the authors to research what happens when such examination shifts from the domain of experts to that of citizens. Drawing on data from this inquiry, which form part of a wider research project, 'Living Data: making sense of health biosensors', we open up conceptual and methodological questions about how to study innovative health technologies and contribute to debates about the direction of health biosensing by bringing forward the views of a group rarely heard in this domain: the public. The panel of 15 participants was shown examples, handled devices and heard evidence about the development of home ovulation monitoring and direct-to-consumer genetic testing. Citizens identified key areas of concern around the development, design and marketing of these devices, implicating technology companies, public bodies and civil society organisations. The panel articulated serious concerns relating to ethics, trust, accountability, quality and governance of health biosensors that operate 'outside the clinic'. Their deliberations reflect concern for what kind of society is being made when genetic testing and home reproductive technologies are promoted and sold directly to the public. The panel process allowed us to re-imagine biosensors, wresting their narratives from the individualising discourses of self-optimisation and responsibilisation which have dominated their introduction in Euro-US markets.